Connecting body of metal material and connecting method of metal material

By connecting metal materials A and B with thermoplastic resin films, the problems of production line pollution, repair difficulties and long process time in the prior art are solved, and efficient, convenient and less polluted metal materials are achieved.

CN119768267APending Publication Date: 2025-04-04RESONAC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380061661.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-26
Filing Date
2023-07-05
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing metal material connection technology has problems such as production line pollution, difficulty in repairing, long process time and large changes in the thickness of the connection part.

Method used

A film with thermoplastic resin as the main component is used to overlap the end of metal material A and the end of metal material B, and the film is melted and solidified by heating, thereby realizing the connection of the metal material.

Benefits of technology

It realizes that there is no need to worry about production line pollution caused by bonding components, can repair connections, short process time, and small changes in the thickness of the connection part, avoiding pollution and complexity in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768267A_ABST
    Figure CN119768267A_ABST
Patent Text Reader

Abstract

A metallic material connection body having an overlapping portion in which an end portion A of a metallic material A and an end portion B of a metallic material B are overlapped with each other with a thin film having a thermoplastic resin as a main component therebetween, the thin film being a thin film that has been melted and solidified in the overlapping portion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a metal material connector in which an end A of a metal material A and an end B of a metal material B are overlapped and connected together, and a metal material connection method suitable for overlapping and connecting an end A of a metal material A and an end B of a metal material B. Background Art

[0002] A method of connecting a starting end of a first coil and a terminal end of a second coil by overlapping and bonding them via a double-sided tape has been disclosed (Patent Document 1).

[0003] When connecting via double-sided tape or single-sided tape (hereinafter collectively referred to as tape), the adhesive components such as the matrix resin and adhesion-imparting agent of the resin composition constituting the adhesive layer of the tape may adhere to the conveying path and mold of the production line and cause contamination of the production line.

[0004] In particular, when the tape is accidentally peeled off, the adhesive layer of the peeled tape is exposed, and the adhesive component adheres to the conveying path and mold of the production line, causing production line contamination, which becomes a serious problem.

[0005] When the metal material is immersed in a chemical bath, the adhesive component such as the adhesive agent dissolves in the chemical bath, and there is also a problem of early contamination of the chemical bath. In addition, there is also a problem of low heat resistance and chemical resistance.

[0006] As other connection means, connection by welding, connection by liquid adhesive, connection by film-like thermosetting adhesive (hereinafter referred to as thermosetting adhesive film), connection by riveting, etc. can be considered, but each has the following problems.

[0007] Once welded, the connection cannot be disassembled without destruction. Therefore, there is a problem that it is not easy to reconnect (hereinafter referred to as repair) in the event of a failure such as a deviation in the connection position. In addition, sparks and metal powders are scattered during welding, which deteriorates the working environment.

[0008] The connection by liquid adhesive requires a coating step of applying a liquid thermosetting resin composition, and a curing step of polymerizing the resin composition after coating to cure it. In the coating step, the coating of the resin composition takes time, and the polymerization reaction takes time in the curing step. In this way, the connection by liquid adhesive has the problem of lack of convenience due to the increase in the process time of the connection. Furthermore, since it is an amorphous liquid, the thickness, coating amount, and coating range of the coating used for connection are difficult to control with good reproducibility. Furthermore, in the case of liquid thermosetting adhesive, as in the case of the aforementioned welding, it cannot be repaired or is difficult to repair.

[0009] In the case of connection by thermosetting adhesive film, no coating step is required, and the process time can be shortened, but the connection cannot be repaired.

[0010] When the thermosetting adhesive film is a B-stage film, since the polymerization reaction easily proceeds at room temperature, the storage stability is not good and it cannot be stored for a long time at room temperature. Therefore, when the thermosetting adhesive film is a B-stage film, it needs to be stored at a low temperature, and a low-temperature storage warehouse is required. It is not easy to store a large amount for a long time, and it lacks convenience.

[0011] In the case of riveting, overlapping metal materials for riveting is accompanied by protrusions caused by riveting. Therefore, due to the increased thickness at the riveting position of the connection, it is difficult to apply to low-profile manufacturing production lines. In addition, riveting requires a space for flat metal materials that is larger than the riveting diameter, and if the metal materials are complex shapes and narrow spacing, there is a problem that sufficient connection strength cannot be obtained. In addition, when passing through multiple liquid tanks, the amount of liquid carried into the next tank increases, which increases the contamination of the liquid and shortens the life of the liquid.

[0012] [Prior art literature]

[0013] [Patent Document]

[0014] [Patent Document 1] Japanese Patent Application Publication No. 2016-175768 Summary of the invention

[0015] [Problems to be Solved by the Invention]

[0016] The present invention is made in view of such technical background, and its object is to provide a connection technology that does not need to worry about production line contamination due to adhesive components, can be repaired, has a short process time, and has little thickness variation in the connection part.

[0017] In order to achieve the aforementioned object, the present invention provides the following method.

[0018] <Metal material connector>

[0019] [1] A metal material connection body having an overlapping portion formed by overlapping an end portion A of a metal material A and an end portion B of a metal material B via a film mainly composed of a thermoplastic resin,

[0020] The film is a film that has been melted and solidified at the overlapping portion.

[0021] [2] The connected body of metal materials as described in [1], wherein the metal material A and the metal material B are at least one selected from a metal plate having a thickness of 1 mm or less and a metal foil having a thickness of 1 mm or less.

[0022] [3] The connected body of metal materials as described in [1] or [2], wherein the metal material A and the metal material B are in the shape of strips, and the metal material A and the metal material B are connected in a continuous manner in the length direction.

[0023] [4] The connected body of metal materials as described in [3], wherein the metal material A and the metal material B are coiled materials formed by winding at least one selected from a metal plate and a metal foil into a roll.

[0024] [5] In the metal material connection body described in any one of [1] to [4], the thin film is disposed over the entire surface of the overlapping surface between the end portion A and the end portion B.

[0025] [6]. The connected body of metal materials according to any one of [1] to [5], wherein the thermoplastic resin is an amorphous thermoplastic resin.

[0026] [7] In the metal material connection body described in [6], the amorphous thermoplastic resin is at least one selected from thermoplastic epoxy resin and phenoxy resin.

[0027] [8] The metal material connection body described in [7], wherein the amorphous thermoplastic resin is an amorphous thermoplastic resin having an epoxy equivalent of 1600 or more, or an amorphous thermoplastic resin containing no epoxy group.

[0028] [9] A metal material connection body as described in any one of [1] to [8], wherein the film has an adhesive,

[0029] The adhesive performs a temporary fixing function of the film but does not perform a bonding function.

[0030] <Methods for joining metal materials>

[0031]

[10] . A method for connecting metal materials, wherein the end A of metal material A and the end B of metal material B are overlapped at an overlapping portion through a film mainly composed of thermoplastic resin, and the film is melted and solidified to connect the metal material A and the metal material B.

[0032]

[11] . The method for connecting metal materials as described in

[10] , wherein the thickness of the film is 10 μm to 3 mm.

[0033] [Effects of the invention]

[0034] According to the present invention, it is possible to provide a connection technology which does not require concern about production line contamination due to adhesive components, is repairable, has a short process time, and has little thickness variation at the connection portion. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] [ Figure 1 ]A plan view of a connection body of metal materials according to one embodiment of the present invention.

[0036] [ Figure 2 ]Plan view of the connection body of metal materials of Comparative Example 1. DETAILED DESCRIPTION

[0037] Hereinafter, embodiments of the present invention will be described in detail.

[0038] In this specification, connection refers to connecting objects to make them continuous, and joining is its subordinate concept. Joining in this specification refers to combining objects in a way that they are in contact with each other, and bonding and welding are its subordinate concepts. Bonding refers to the process of bringing two adhered objects (objects to be bonded) into a bonded state through an organic material (thermosetting resin, thermoplastic resin, etc.) such as a tape or adhesive. Welding refers to the process of melting the surface of a thermoplastic resin, etc. by heat, and cooling it, thereby entangled by molecular diffusion to form a bonded state.

[0039] [Metal material connector]

[0040] The metal material connection body has an overlapped portion 4 where an end portion A:5 of a metal material A:1 and an end portion B:6 of a metal material B:2 overlap each other via a film 3 mainly composed of a thermoplastic resin (hereinafter simply referred to as "film"). The film 3 is a film melted and solidified at the overlapped portion 4.

[0041] The linker of this embodiment is as follows Figure 1 As shown, there is an "overlapping portion 4" where an end portion B:6 of a metal material B:2 is placed and overlapped on an end portion A:5 of a metal material A:1 with the film 3 interposed therebetween.

[0042] In this specification, "main component" refers to the component with the highest content among the resin components in the film. The film preferably contains 50% by mass or more of the resin component, more preferably 70% by mass or more, more preferably 80% by mass or more, and particularly preferably 90% by mass or more.

[0043] The film 3 is melted and solidified at the overlapped portion 4, and the film 3 is bonded to the end portion A:5 of the metal material A:1, and the film 3 is bonded to the end portion B:6 of the metal material B:2, thereby connecting the aforementioned metal material A:1 and the aforementioned metal material B:2 to form a connected body. The connected body of the present invention obtained by melting and solidifying the film at the overlapped portion 4 shows excellent connection strength.

[0044] The connection strength is affected by many factors, such as the thickness of the film, the molecular weight of the polymer constituting the film, the chemical structure, the mechanical properties, and the viscoelastic properties, in addition to the strength of the interface interaction between the aforementioned film and the metal material. The mechanism by which the connector of the present invention exhibits excellent connection strength is still unclear. It is speculated that the main reason is the formation of chemical bonds and intermolecular forces such as hydrogen bonds and van der Waals forces at the interface between the film and the metal material A, and between the film and the metal material B. However, since the state or characteristics of the interface between the film and the metal material in the aforementioned connector need to be defined by analyzing the chemical structure of the ultra-thin interface below the nanometer level, it is impossible or impractical to define the connector of the present invention by directly defining the state or characteristics of the interface between the film and the metal material with the current technology.

[0045] The connected body of the present invention is connected by the melted and solidified film 3 at the overlapped portion 4. The melted and solidified film 3 at the overlapped portion 4 can be distinguished from the film before melted and solidified by the presence or absence of roundness of the film corners and the presence or absence of thickness deviation.

[0046] The film before melting and solidification has a sharp cut surface formed in the manufacturing process of the film. The film 3 constituting the connector of the metal material of the present invention is the film 3 after melting and solidification in the overlapping portion 4, so it is presumed that it does not have a sharp cut surface formed in the manufacturing process of the film, and the corners of the film are rounded.

[0047] Since the film is usually manufactured in a manner to have a uniform thickness, no thickness deviation is observed in the film before melting and solidification. However, the film 3 constituting the connector of the metal material of the present invention is a film 3 melted and solidified at the overlapping portion 4, and it is presumed that there is an inevitable thickness deviation generated during the aforementioned melting and solidification process. As a method for measuring thickness deviation, any appropriate method such as measuring the thickness of any multiple points in the surface of the measured object and performing statistical processing can be adopted. As such a method for measuring thickness, for example, a method accompanied by physical contact such as a micrometer, a micrometer caliper, a micrometer gauge, etc.; a non-contact method of measuring the transmittance and reflectivity of α-rays, X-rays, infrared rays, electromagnetic waves, etc. irradiated to the measured object; a method of cutting the measured object at an arbitrary position and observing it with an optical microscope or an electron microscope, etc., and a combination of these methods can also be used.

[0048] It is estimated that the film 3 after being melted and solidified at the overlapping portion 4 has the surface properties of the end A:5 transferred to the film surface in contact with the end A:5 of the metal material A:1, and the surface properties of the end B:6 transferred to the film surface in contact with the end B:6 of the metal material B:2. Here, the surface properties refer to the fine irregularities generated on the surface of the metal material during the process of machining the metal material, etc.

[0049] The connection of the present invention is a connection that utilizes the phase change (solid-liquid-solid) of a film mainly composed of a thermoplastic resin, and is not accompanied by a chemical reaction such as a polymerization reaction. Since the aforementioned film is used in a state where the polymerization reaction has been completed, the polymerization reaction does not proceed even at room temperature, and it can be stored for a long time at room temperature. Since the aforementioned film can be softened and melted by heat, it is easy to peel off and has excellent disassembly properties. Furthermore, since the aforementioned film has the property of thermoplasticity, it can be repeatedly and reversibly softened, melted and solidified, and has excellent repairability. The connection using the aforementioned film utilizes the phase change (solid-liquid-solid) of the film, and can be completed in a shorter time than a polymerization reaction accompanied by the formation of chemical bonds, and has the advantage of a short process time. The aforementioned film is not a liquid at room temperature, but a solid after the polymerization reaction has been completed. Since the bonding is carried out by a mechanism different from bonding, it is not necessary to use an adhesive containing an adhesive component for bonding purposes, and there is no need to worry about contamination of the production line caused by the adhesive component. Since the aforementioned film has completed the polymerization reaction, it also has excellent heat resistance and chemical resistance. Furthermore, since a thin film is used for connection, there is an advantage that the thickness variation at the connection portion is small compared to riveting or the like.

[0050] The connection body is preferably formed by the thin film 3 interposed over the entire surface of the overlapping surface between the end portion A:5 of the metal material A:1 and the end portion B:6 of the metal material B:2.

[0051] <Metal Materials>

[0052] The shapes of the metal material A and the metal material B are not particularly limited as long as they are flat plates. The present invention is suitable for the purpose of connecting at least one selected from a metal plate with a thickness of 1 mm or less and a metal foil with a thickness of 1 mm or less. The metal material A and the previous metal material B are both in the form of strips (long strips), and are suitable for overlapping the end A of the metal material A and the end B of the metal material B to connect them in a continuous manner in the length direction. Specifically, it is suitable for the purpose of connecting coils wound into a coil of metal foil, and is particularly suitable for connecting the end of the previous coil fed into the production line with the front end of the next coil, and for connecting the end and the front end when there is a coil gap in the coil.

[0053] In this specification, metal foil refers to a material obtained by stretching a highly ductile metal into a thin paper-like shape.

[0054] There is no special limitation on the types of metals used in metal material A and metal material B. Preferably, they are at least one selected from aluminum, iron, copper, magnesium and alloys thereof. From the perspective of the strength of the interfacial adhesion with the aforementioned film, if they are at least one selected from aluminum alloy and iron alloy, a strong connection can be achieved, which is particularly preferred.

[0055] Furthermore, the surface of at least one selected from the metal material A and the metal material B may be subjected to metal plating treatment or may be coated with a resin.

[0056] Examples of the resin include polyolefins and acid-modified products thereof, polystyrene, polymethyl methacrylate, AS resins, ABS resins, thermoplastic aromatic polyesters such as polyethylene terephthalate and polybutylene terephthalate, polycarbonates, polyimides, polyamides, polyamide-imides, polyetherimides, polyether sulfones, polyphenylene ethers and modified products thereof, polyphenylene sulfide, polyoxymethylene, polyarylates, polyether ketones, polyether ether ketones, polyether ketone ketones, and thermoplastic epoxy resins.

[0057] The position of the metal material A and the metal material B in contact with the film can obtain high adhesion between the film and the metal material by performing pretreatment. As the pretreatment, it is preferred to clean the surface of the metal material or to give the surface a concave-convex treatment. When the metal material is composed of aluminum or iron, it is suitable to be a pretreatment selected from at least one of degreasing treatment, UV ozone treatment, sandblasting, grinding treatment, plasma treatment, and etching treatment.

[0058] Only one type of pretreatment may be performed, or two or more types may be performed. As specific methods of these pretreatments, well-known methods can be used.

[0059] <Film>

[0060] In the present specification, a film refers to a product obtained by molding a resin mainly composed of a thermoplastic resin into a thin film or a product obtained by molding a resin composition mainly composed of a thermoplastic resin into a thin film.

[0061] From the viewpoint of sufficiently imparting thermoplastic resin properties to the film, the content of the thermoplastic resin is preferably 60% by mass or more, more preferably 70% by mass or more, more preferably 80% by mass or more, and most preferably 90% by mass or more of the resin components in the film.

[0062] The thermoplastic resin is preferably an amorphous thermoplastic resin. In the present embodiment, the amorphous thermoplastic resin refers to a resin having no crystals or a very small amount of crystals, specifically, a crystal having a heat of fusion of 15 J / g or less.

[0063] The heat of fusion is calculated from the area of ​​the endothermic peak of DSC (differential scanning calorimeter) and the weight of the thermoplastic resin component. When the film contains an inorganic filler, etc., the inorganic filler is deducted and the heat of fusion is calculated from the weight of the thermoplastic resin component. Specifically, 2-10 mg of the sample is weighed and placed on an aluminum plate. Using DSC (DSC8231 manufactured by Rigaku Co., Ltd.), the temperature is raised from 23°C to 200°C or more at a rate of 10°C / min to obtain a DSC curve. Then, the heat of fusion can be calculated from the area of ​​the endothermic peak at the time of melting obtained from the DSC curve and the weighed value.

[0064] The heat of fusion is preferably 11 J / g or less, more preferably 7 J / g or less, still more preferably 4 J / g or less, and most preferably the melting peak is below the detection limit.

[0065] The film mainly composed of an amorphous thermoplastic resin with a melting heat of 15 J / g or less does not undergo a rapid viscosity drop as observed in conventional hot melt adhesives when heated to melt, and does not reach a low viscosity (0.001 to 100 Pa·s) state even in a high temperature range exceeding 200° C. Therefore, the film does not melt and flow out, and the thickness after solidification can be maintained within a predetermined range, so that a high connection strength can be stably obtained.

[0066] When the amorphous thermoplastic resin as the main component of the film contains a small amount of crystals, the melting point is preferably 50 to 400° C., more preferably 60 to 350° C., and even more preferably 70 to 300° C. When the melting point is in the range of 50 to 400° C., the film is effectively deformed and melted by heating, and high bonding strength can be obtained by effectively wetting and spreading on the respective bonding surfaces of the film and the metal material A and the film and the metal material B.

[0067] In this specification, the melting point of a thermoplastic resin refers to the melting peak temperature measured by DSC. In addition, when a melting peak cannot be obtained and when the heat of fusion is 15 J / g or less, the melting point is the temperature of the glass transition temperature plus 70°C. The glass transition temperature refers to the temperature at which the DSC curve of the second cycle of heating to 200°C by DSC, cooling to 40°C or less, and then heating to 200°C begins to decrease.

[0068] The amorphous thermoplastic resin is preferably at least one selected from thermoplastic epoxy resins and phenoxy resins. Thermoplastic epoxy resins and phenoxy resins have low cohesive force within the resin and strong interaction with metal materials, and can connect metal materials with a higher connection force than conventional crystalline hot melt adhesives. Furthermore, since thermoplastic epoxy resins and phenoxy resins have excellent flexibility and toughness, high-strength connections can be obtained.

[0069] The amorphous thermoplastic resin has an epoxy equivalent of 1,600 or more, and preferably contains no epoxy group.

[0070] The epoxy equivalent (weight of the thermoplastic resin containing 1 mol of epoxy groups) is the value of the epoxy equivalent of the thermoplastic resin contained in the film before connection, and is a value measured according to the method specified in JIS-K 7236:2001 (unit: "g / eq."). Specifically, a potentiometric titration apparatus is used, tetraethylammonium bromide acetic acid solution is added, and a 0.1 mol / L perchloric acid-acetic acid solution is used. The solvent-diluted product (resin varnish) is a value calculated by calculating the solid content conversion value based on the non-volatile content. In the case of a mixture of two or more resins, it can also be calculated based on the respective contents and epoxy equivalents.

[0071] The epoxy equivalent of the amorphous thermoplastic resin is more preferably 2,000 or more, further preferably 5,000 or more, and even more preferably 9,000 or more, and most preferably exceeds the detection limit and substantially no epoxy group is detected. The epoxy equivalent exceeding the detection limit means that no epoxy group is detected when the epoxy equivalent is measured based on JIS K 7236:2001 described below.

[0072] By using a film containing as a main component an amorphous thermoplastic resin having an epoxy equivalent of 1,600 or more, a rapid decrease in viscosity can be more effectively suppressed, and a higher bonding strength can be stably obtained.

[0073] 《Thermoplastic Epoxy Resin》

[0074] The thermoplastic epoxy resin is preferably a polymer of (a) a bifunctional epoxy resin monomer or a bifunctional epoxy resin oligomer and (b) a bifunctional compound having two identical or different functional groups selected from phenolic hydroxyl groups, carboxyl groups, mercapto groups, isocyanate groups and cyanate groups.

[0075] By using such a compound, the polymerization reaction to form a linear polymer proceeds preferentially, and a thermoplastic epoxy resin having desired properties can be obtained.

[0076] The (a) bifunctional epoxy resin monomer refers to an epoxy resin monomer having two epoxy groups in the molecule, and the bifunctional epoxy resin oligomer refers to an epoxy resin oligomer having two epoxy groups in the molecule.

[0077] Specific examples of the above (a) include, for example, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bifunctional phenol novolac type epoxy resins, bisphenol AD ​​type epoxy resins, biphenyl type epoxy resins, bifunctional naphthalene type epoxy resins, bifunctional alicyclic epoxy resins, bifunctional glycidyl ester type epoxy resins (e.g., diglycidyl phthalate, diglycidyl tetrahydrophthalate, diglycidyl dimer acid diglycidyl ester, etc.), bifunctional glycidyl amine type epoxy resins (e.g., diglycidyl aniline, diglycidyl toluidine, etc.), bifunctional heterocyclic epoxy resins, bifunctional diaryl sulfone type epoxy resins, hydroquinone type epoxy resins (e.g., hydroquinone diglycidyl ether, 2,5-di-tert-butyl ether, etc.), butylhydroquinone diglycidyl ether, resorcinol diglycidyl ether, etc.), bifunctional alkylene glycidyl ether compounds (for example, butanediol diglycidyl ether, butenediol diglycidyl ether, butynediol diglycidyl ether, etc.), bifunctional glycidyl hydantoin compounds (for example, 1,3-diglycidyl-5,5-dialkylhydantoin, 1-glycidyl-3-(glycidoxyalkyl)-5,5-dialkylhydantoin, etc.), bifunctional glycidyl siloxanes (for example, 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane, α,β-bis(3-glycidoxypropyl)polydimethylsiloxane, etc.), and modified products thereof. Among them, bisphenol A type epoxy resin, bisphenol F type epoxy resin, and biphenyl type epoxy resin are preferred from the viewpoint of reactivity and handling properties.

[0078] Examples of the bifunctional compound having a phenolic hydroxyl group of the aforementioned (b) include mononuclear aromatic dihydroxy compounds having one benzene ring such as catechol, resorcinol, and hydroquinone, bisphenols such as bis(4-hydroxyphenyl)propane (bisphenol A), bis(4-hydroxyphenyl)methane (bisphenol F), and bis(4-hydroxyphenyl)ethane (bisphenol AD), compounds having a condensed ring such as dihydroxynaphthalene, bifunctional phenol compounds into which an allyl group is introduced such as diallylresorcinol, diallylbisphenol A, and triallyldihydroxybiphenyl, and dibutylbisphenol A.

[0079] Specific examples of the carboxyl group-containing compound (b) include adipic acid, succinic acid, malonic acid, cyclohexanedicarboxylic acid, phthalic acid, isophthalic acid, and terephthalic acid.

[0080] Examples of the bifunctional compound having a mercapto group (b) include ethylene glycol dithioacetate and ethylene glycol dithiopropionate.

[0081] Specific examples of the isocyanate group-containing bifunctional compound (b) include diphenylmethane diisocyanate (MDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HMDI), and toluene diisocyanate (TDI).

[0082] Specific examples of the cyanate group-containing bifunctional compound (b) include 2,2-bis(4-cyanophenyl)propane, 1,1-bis(4-cyanophenyl)ethane, and bis(4-cyanophenyl)methane.

[0083] Among the above (b), a bifunctional compound having a phenolic hydroxyl group is preferred from the viewpoint of obtaining a thermoplastic polymer, a bifunctional compound having two phenolic hydroxyl groups and having a bisphenol structure or a biphenyl structure is preferred from the viewpoint of heat resistance and connectivity, and at least one selected from bisphenol A, bisphenol F and bisphenol S is preferred from the viewpoint of heat resistance and cost.

[0084] When the aforementioned (a) is a bisphenol A type epoxy resin, a bisphenol F type epoxy resin, a bisphenol S type epoxy resin, or a biphenyl type epoxy resin, and the aforementioned (b) is at least one selected from bisphenol A, bisphenol F, and bisphenol S, the polymer obtained by polymerizing the aforementioned (a) and (b) has a p-phenylene structure and an ether bond as the main skeleton, and has a main chain in which these are connected by an alkylene group, and a hydroxyl group generated by the multiple addition is arranged on the side chain.

[0085] The linear structure formed by the paraphenylene skeleton can improve the mechanical strength of the polymer after polymerization, and the hydroxyl group arranged in the side chain can improve the adhesion to metal materials. As a result, the adhesiveness of the thermosetting resin can be maintained and high connection strength can be achieved. Furthermore, in the case of a thermoplastic resin, it can be softened and melted by heat to become recyclable and repairable, and the recyclability and repairability of the problematic points in the thermosetting resin can be improved.

[0086] 《Phenoxy resin》

[0087] Phenoxy resin is a polyhydroxy polyether synthesized by bisphenols and epichlorohydrin, and has thermoplasticity. In the manufacture of phenoxy resin, there are known methods of directly reacting dihydric phenols with epichlorohydrin, and methods of performing addition polymerization reaction between dihydric phenols and dihydric phenols by diglycidyl ether. The phenoxy resin used in the present invention can be obtained by any method. In the case of direct reaction of dihydric phenols with epichlorohydrin, as dihydric phenols, for example, phenols such as bisphenol A, bisphenol F, bisphenol S, biphenol, biphenylene glycol, diphenylfluorene, etc.; aliphatic diols such as ethylene glycol, propylene glycol, and diethylene glycol can be listed. From the viewpoint of cost, connectivity, viscosity, and heat resistance, bisphenol A, bisphenol F, and bisphenol S are preferred. They can be used alone or in combination of two or more.

[0088] Phenoxy resin has a chemical structure similar to that of epoxy resin, and has a p-phenylene structure and an ether bond as a main skeleton, a main chain connecting them, and a hydroxyl group arranged on a side chain.

[0089] 《Physical properties of thermoplastic epoxy resin and phenoxy resin》

[0090] The weight average molecular weight of the thermoplastic epoxy resin and phenoxy resin measured by GPC (gel permeation chromatography) in terms of polystyrene conversion is preferably 10,000 to 500,000, more preferably 18,000 to 300,000, and even more preferably 20,000 to 200,000. The weight average molecular weight is a value of the molecular weight converted to standard polystyrene, calculated based on the position of the elution peak detected by GPC. When the weight average molecular weight is within this value range, the balance between thermoplasticity and heat resistance is excellent, and a connector can be effectively obtained by melting, and the heat resistance is also high. When the weight average molecular weight is 10,000 or more, the heat resistance is excellent, and when it is 500,000 or less, the viscosity during melting is low and the connectivity is high.

[0091] 《Ingredients other than resin components in films》

[0092] The film may contain fillers and additives as necessary, but may not contain fillers and additives as components other than the resin component, within the range not hindering the purpose of the present invention.

[0093] Examples of the filler include inorganic fillers and organic fillers (resin powders).

[0094] Examples of the inorganic filler include spherical fused silica, metal powders such as iron, silica sand, talc, calcium carbonate, mica, acid clay, diatomaceous earth, kaolin, quartz, titanium oxide, silicon dioxide, phenolic resin microcapsules, and glass hollow spheres.

[0095] When the film contains fillers, the content of the fillers in the total volume 100% by volume of the film is preferably 50% by volume or less, more preferably 30% by volume or less, still more preferably 20% by volume or less, and most preferably 10% by volume or less. Furthermore, the volume of the filler can be obtained by dividing the weight of the filler contained in the film by the apparent specific gravity of the filler.

[0096] The content of the resin component in the total volume 100% by volume of the film is preferably 10% by volume or more, more preferably 20% by volume or more, even more preferably 30% by volume or more, even more preferably 50% by volume or more, in one embodiment it is 80% by volume or more, in another embodiment it is 90% by volume or more, and in yet another embodiment it is 99% by volume or more.

[0097] Examples of the additives include defoaming agents, coupling agents such as silane coupling agents, and pigments, and these may be contained alone or in combination of two or more.

[0098] The content of the additive in the film is preferably 10% by mass or less, more preferably 5% by mass or less, and still more preferably 1% by mass or less.

[0099] The content of the resin component in the film is preferably 10% by mass or more, more preferably 20% by mass or more, further more preferably 30% by mass or more, further more preferably 50% by mass or more, in one embodiment it is 80% by mass or more, in another embodiment it is 90% by mass or more, and in yet another embodiment it is 99% by mass or more.

[0100] 《Morphology and physical properties of thin films》

[0101] The thickness of the film before bonding is preferably 10 μm to 3 mm.

[0102] The film is set to have a thickness of 10 μm to 3 mm, and heating, pressing, etc. are efficient, and the bonding surfaces between the film and the metal material A and between the film and the metal material B can be expanded to obtain a high connection strength.

[0103] The thickness of the film before bonding is preferably 1 mm or less, more preferably 0.5 mm or less, further preferably 0.3 mm or less, particularly preferably 0.2 mm or less, and most preferably 0.1 mm or less, from the viewpoint of obtaining a connected body with excellent connectivity in a short process time.

[0104] The thickness of the thin film before bonding is more preferably 10 μm or more, more preferably 20 μm or more, and still more preferably 30 μm or more, from the viewpoint of workability.

[0105] The film may be a single layer or a laminate formed of multiple layers. From the perspective of ease of manufacture and improvement of bonding strength, the layer of the thermoplastic resin is preferably a single layer. It may also be a film substrate composed of a resin having a higher melting point than the resin composition, wherein multiple layers of the thermoplastic resin are laminated. In this case, when the metal substrate is heated and welded, the resin film substrate will not melt and the thickness of the resin film substrate will remain, so that a good bonding strength can be maintained.

[0106] Furthermore, the film may have adhesiveness within a range that does not hinder the bonding force and heat resistance.

[0107] The adhesiveness can be imparted by mixing a tackifier into a thermoplastic resin, or by applying an adhesive containing an adhesive component such as an adhesive imparting agent to the film. The aforementioned adhesive is preferably capable of temporarily fixing the aforementioned film, but not achieving a bonding function. An adhesive that achieves a temporary fixing function of the film but not a bonding function refers to, for example, an adhesive that stays within the surface of the bonding surface and does not appear outside the surface.

[0108] The adhesive may be applied to the entire surface of the joint, or may be applied to a portion of the joint in the form of stripes, dots, grids, tiles (a shape in which a plurality of squares are arranged with gaps), etc. The smaller the application area, the lower the viscosity, and the risk of the adhesive being exposed from the end surface of the film to the outside after connection, which may become a contamination factor, can be reduced.

[0109] Conventional adhesive tapes only bear the bonding force between the metal material and the film by the adhesiveness of the adhesive layer of the adhesive tape. In the case of the aforementioned thermoplastic film, since the bonding force is borne by the bonding of the melting and solidification of the thermoplastic resin as described above, the adhesiveness is preferably to the extent of the aforementioned temporary fixing function. That is, when the aforementioned film is arranged between metal materials, the aforementioned film does not need to stick to the metal material, and when a shearing force is applied, the resistance becomes large (not easy to slide).

[0110] When the purpose is to impart tackiness sufficient to provide a temporary fixing function, the amount of adhesive applied is preferably kept to a minimum sufficient to temporarily fix the film (to prevent slipping).

[0111] In the case of conventional tapes, if there is a protruding adhesive layer at the end of the joint surface, there is a risk that the adhesive component will adhere to the conveying path and mold of the production line, causing contamination. Furthermore, if the tape is peeled off in the production line for some reason, the adhesive layer will be exposed, and there is a risk that the adhesive component will adhere to the conveying path and mold of the production line, causing contamination.

[0112] Furthermore, the end faces of the strip-shaped metal material are not necessarily straight lines. In this case, when making a connection body in which the metal material and the double-sided tape are overlapped and bonded, the straight double-sided tape and the strip-shaped metal material cannot completely overlap, resulting in a connection body with either (a) the double-sided tape exposed or (b) the presence of an unbonded metal material portion. In the case of (a) above, the adhesive component sometimes adheres to the conveying path and mold of the production line, causing contamination. In the case of (b) above, the liquid medicine is easily retained in the unbonded portion, and when passing through multiple liquid medicine layers, the liquid medicine is carried in more, and sometimes the contamination of the liquid medicine layer is accelerated.

[0113] According to the present invention, the bonding force is borne by the melting and solidification of the thermoplastic resin. Since no adhesive is required for bonding purposes, even when an adhesive is used for the purpose of determining a position, it can be completed with a minimum of adhesive, and the above-mentioned problems of the conventional tape can be avoided.

[0114] The breaking strength of the thin film in the connected body of the metal material A and the metal material B connected by the thin film is preferably 20 to 1000 N / 25 mm.

[0115] The breaking strength of the film in the connected body is more preferably 50 to 1000 N / 25 mm, and most preferably 100 to 1000 N / 25 mm.

[0116] The breaking strength when the metal material A and the metal material B are connected using the film is the tensile strength at break per 25 mm of the film width measured under the conditions described in the Examples.

[0117] 《Thin film manufacturing method》

[0118] There is no particular limitation on the method for producing a film with a thermoplastic resin as the main component. For example, a monomer or oligomer of a bifunctional epoxy compound may be heated to polymerize to obtain a resin composition, a solvent may be added to the obtained resin composition as needed, the resin composition may be coated on a release film, cured and dried, and pressurized as needed to obtain a film. Furthermore, the polymerization reaction may be carried out after coating on a release film or after obtaining a film, and these may be combined.

[0119] [Methods for joining metal materials]

[0120] The method for manufacturing a connected body according to the present embodiment comprises the following steps: at an overlapped portion 4 where an end portion A:5 of a metal material A:1 and an end portion B:6 of a metal material B:2 overlap with a film having a thermoplastic resin as a main component, the film is melted and solidified to connect the metal material A and the metal material B. By melting and solidifying the film at the overlapped portion 4, the film 3 and the end portion A:5 of the metal material A:1 are bonded, and the film 3 and the end portion B:6 of the metal material B:2 are bonded, thereby connecting the metal material A and the metal material B.

[0121] The metal material and the thin film are the same as those constituting the aforementioned connected body, and their description is omitted here.

[0122] <Thin film melting and solidification>

[0123] The method for melting the film is not particularly limited as long as the film can be heated and melted. Specifically, melting by at least one method selected from contact heating, warm air heating, hot pressing, pulse heating, hot plate welding, infrared heating, ultrasonic welding, vibration welding, and high-frequency induction welding can be cited. From the viewpoint of ease of production and shortening the process, melting by at least one method selected from pulse heating and hot pressing is more preferred.

[0124] In the case of hot pressing, heating and pressing are preferably performed under the conditions of 100 to 400° C. and 0.001 to 20 MPaG.

[0125] The heating condition is preferably 100 to 300° C., more preferably 120 to 250° C., and most preferably 150 to 220° C. By heating at 100 to 400° C., the film is efficiently deformed and melted, and the film is effectively wetted and spread on the respective bonding surfaces of the film and the metal material A and the film and the metal material B, thereby obtaining a high connection strength.

[0126] The pressurization condition is more preferably 0.001 to 20 MPaG, more preferably 0.005 to 10 MPaG, and most preferably 0.01 to 5 MPaG. By applying a pressure of 0.001 to 20 MPaG, the film is efficiently deformed and wetted and spread effectively, thereby obtaining a high connection strength.

[0127] By melting and solidifying the thin film, the thin film and the metal material A are bonded together, and the thin film and the metal material B are bonded together, respectively, so that the metal material A and the metal material B are connected.

[0128] In the case of ultrasonic welding, the transmission frequency is more preferably 10 to 70 kHz, more preferably 15 to 40 kHz.

[0129] The ultrasonic wave application time is more preferably 0.1 to 3 seconds, and more preferably 0.2 to 2 seconds, from the viewpoint of adhesiveness and appearance.

[0130] When pressure is applied while applying ultrasound, the pressure is preferably 0.01 to 20 MPaG, more preferably 0.1 to 10 MPaG, and even more preferably 0.2 to 5 MPaG. In this pressure range, the film deforms efficiently, wets and spreads effectively on the bonding surface, and high bonding strength can be obtained.

[0131] In the case of high-frequency induction welding, the output may be in the range of 100 to 5000 W, and the oscillation time may be adjusted according to the size and type of the resin substrate, and is preferably 1.0 to 10.0 seconds, and more preferably 1.5 to 8.0 seconds.

[0132] The method of solidifying the melted film may be a method of cooling at room temperature or a method of cooling using a cooling device. In addition, "room temperature" refers to a general room temperature in the range of 5 to 30° C. From the viewpoint of ease of production, a method of cooling at room temperature is more preferred.

[0133] In this specification, solidification means being solid at room temperature, that is, having no fluidity under no pressure at 23° C. However, the solidified film may also have viscous properties.

[0134] [Example]

[0135] Specific examples of the present invention will be described below, but the present invention is not limited to these examples.

[0136] <Metal material A and metal material B>

[0137] As the metal material A and the metal material B, C1100 (tough pitch copper) having a width of 25 mm, a length of 100 mm, and a thickness of 0.1 mm was prepared.

[0138] <Weight average molecular weight, heat of fusion and epoxy equivalent of thermoplastic epoxy resin and phenoxy resin>

[0139] The weight average molecular weight, heat of fusion, and epoxy equivalent of the thermoplastic epoxy resin and the phenoxy resin were respectively determined as follows.

[0140] (Weight average molecular weight)

[0141] A thermoplastic epoxy resin or a phenoxy resin is dissolved in tetrahydrofuran, and the measurement is performed under the following conditions using Prominence 501 (manufactured by Showa Science Co., Ltd., detector: Shodex (registered trademark) RI-501 (manufactured by Showa Denko K.K.)).

[0142] Pipe column: LF-804 manufactured by Showa Denko K.K. × 2 pieces

[0143] Column temperature: 40℃

[0144] Sample: 0.4 mass% tetrahydrofuran solution of resin

[0145] Flow rate: 1ml / min

[0146] Eluent: Tetrahydrofuran

[0147] Calibration method: converted to standard polystyrene

[0148] (Heat of Fusion)

[0149] 2 to 10 mg of a thermoplastic epoxy resin or phenoxy resin is weighed and placed on an aluminum plate, and the temperature is raised from 23°C to 200°C at 10°C / min using a DSC (DSC8231 manufactured by Rigaku Corporation) to obtain a DSC curve. The heat of fusion is calculated from the area of ​​the endothermic peak during melting of the DSC curve and the weighed value.

[0150] (Epoxy Equivalent Weight)

[0151] The value was measured in accordance with JIS K-7236: 2001 and converted to a value as a resin solid content. In the case of a simple mixture without reaction, it was calculated based on the epoxy equivalent and content of each.

[0152] <Example 1>

[0153] (Film P-1)

[0154] In a reaction apparatus equipped with a stirrer, a reflux condenser, a gas introduction tube and a thermometer, 1.0 equivalent (203 g) of jER (registered trademark) 1007 (manufactured by Mitsubishi Chemical Co., Ltd., bisphenol A type epoxy resin, weight average molecular weight 10,000), 1.0 equivalent (12.5 g) of bisphenol S, 2.4 g of triphenylphosphine and 1,000 g of methyl ethyl ketone were placed, and the mixture was heated to 100° C. while stirring under a nitrogen atmosphere. The mixture was visually confirmed to have dissolved, and then cooled to 40° C. to obtain a resin composition having a solid content of about 20% by mass. The solvent was removed to obtain a solid. A non-adhesive fluororesin film (NITOFLON (registered trademark) No. 900UL, manufactured by Nitto Denko Corporation) was set on the upper and lower plates of the press, and the aforementioned solid was arranged on the non-adhesive fluororesin film of the lower plate, and then the aforementioned press was heated to 160°C, and the aforementioned resin composition was heated and compressed for 2 hours to obtain a film P-1 with a thickness of 100 μm and a solid content of 100% by mass. The weight-average molecular weight is about 37,000. The epoxy equivalent exceeds the detection limit (that is, there is almost no epoxy group). No melting heat peak was detected in DSC, confirming that it is amorphous.

[0155] (Connector)

[0156] The end B of the metal material B was overlapped on the end A of the metal material A via the aforementioned film P-1 cut to a size of 20×25 mm, and placed on a hot plate set at 200°C. The overlapped position via the aforementioned film P-1 was formed by placing the metal material A on the hot plate, placing a 3×3 cm glass plate on the metal material B, and placing a load of 2 kg on the glass plate for 1 minute. After the aforementioned welding, the aforementioned glass plate and the load were removed, and the aforementioned film P-1 was cooled to room temperature.

[0157] <Example 2>

[0158] (Film P-2)

[0159] In a reaction apparatus equipped with a stirrer, a reflux condenser, a gas inlet pipe and a thermometer, 20 g of PhenoTohto (registered trademark) YP-50S (manufactured by NIPPON STEEL Chemical & Material Co., Ltd., phenoxy resin, weight average molecular weight 50,000) and 80 g of cyclohexanone were placed, and the temperature was raised to 60°C while stirring. Visually confirming that it has dissolved, the resin composition was cooled to 40°C to obtain a resin composition with a solid content of 20% by mass. The above-mentioned resin composition was applied to a release film and dried at 120°C for 30 minutes to obtain a film P-2 with a solid content of 100% by mass and a thickness of 100 μm. The epoxy equivalent exceeded the detection limit (that is, there was almost no epoxy group). No melting heat peak was detected in DSC, confirming that it was amorphous.

[0160] (Connector)

[0161] A connected body was produced in the same manner as in Example 1 except that P-2 was used as the thin film.

[0162] <Example 3>

[0163] (Film P-3)

[0164] In a reaction apparatus equipped with a stirrer, a reflux condenser, a gas inlet pipe and a thermometer, 20 g of PhenoTohto (registered trademark) YPS-007A (manufactured by NIPPON STEEL Chemical & Material Co., Ltd., phenoxy resin, weight average molecular weight 42,000) and 80 g of cyclohexanone were placed, and the temperature was raised to 60°C while stirring. Visually confirming that it has dissolved, the resin composition was cooled to 40°C to obtain a resin composition with a solid content of 20% by mass. The above-mentioned resin composition was applied to a release film and dried at 120°C for 30 minutes to obtain a film P-3 with a solid content of 100% by mass and a thickness of 100 μm. The epoxy equivalent exceeded the detection limit (that is, there was almost no epoxy group). No melting heat peak was detected in DSC, confirming that it was amorphous.

[0165] (Connector)

[0166] A connected body was produced in the same manner as in Example 1 except that P-3 was used as the thin film.

[0167] <Example 4>

[0168] (Connector)

[0169] A connected body was prepared in the same manner as in Example 1 except that a crystalline olefin hot melt adhesive film (ELPHAN (registered trademark) NT-120 manufactured by Nihon Matai Co., Ltd., thickness before connected body preparation 80 μm) was used as the film and the temperature of the hot plate was set to 150° C. The melting heat peak in DSC was 60 J / g.

[0170] <Comparative Example 1>

[0171] (Connector)

[0172] Two pieces of tape cut to a size of 30×25 mm (Sekisui Sero Tape (registered trademark) No. 252 manufactured by Sekisui Chemical Co., Ltd., thickness 50 μm before forming the connected body) were used. Figure 2 As shown, an end portion B of a metal material B is attached to an end portion A of a metal material A so as to cover both surfaces of an overlapping portion overlapping in a range of 25 mm in width and 20 mm in length, thereby manufacturing a connected body.

[0173] <Comparative Example 2>

[0174] (Connector)

[0175] On the end A of the metal material A, a double-sided tape (NITOMS PROSELF, manufactured by NITOMS Co., Ltd.) cut to a size of 20×25 mm is placed, and the end B of the metal material B is overlapped. A 3×3 cm glass plate is placed on the end B, and a load of 2 kg is placed on the glass plate and left to stand for 1 minute, and then the load is removed to produce a connector.

[0176] <Comparative Example 3>

[0177] (Connector)

[0178] A connected body was produced in the same manner as in Comparative Example 2 except that a heat-resistant double-sided tape (polyimide tape PB416-20-30AS manufactured by ONE Co., Ltd.) cut into a size of 20×25 mm was used as the tape.

[0179] [Breaking strength measurement_Tensile test]

[0180] The tensile strength of the connected bodies obtained in Examples 1 to 4 and Comparative Examples 1 to 3 was measured. The measurement conditions were: using a universal testing machine Autograph AG-X Plus manufactured by Shimadzu Corporation, with a distance between the clamps set to 13 cm and a tensile speed set to 5 mm / min. The measurement results (breaking strength) are shown in Table 1.

[0181] The measurements were performed under the conditions of "normal temperature: 23°C" and "ethylene glycol immersion". In Table 1, the values ​​measured under the "ethylene glycol immersion" condition are the values ​​measured at normal temperature after immersion in ethylene glycol at 40°C for 5 days, taking out, immersing in water for 5 seconds, wiping off the ethylene glycol, photographing the appearance, and leaving it to stand for 20 to 30 minutes.

[0182] [Production line contamination]

[0183] Evaluate the possibility of contamination of the production line due to adhesive components.

[0184] As described in the background technology section, the contamination of the production line becomes a major problem when the connection is performed by tape, especially when the tape is accidentally peeled off in the production line. Therefore, in this evaluation, after the aforementioned tensile test, the layer containing the adhesive component is observed to see if it is exposed in the state where the metal materials A and B are separated, and the production line contamination is evaluated.

[0185] Specifically, after the tensile test, when the metal materials A and B were separated, the layer containing the adhesive component was exposed and evaluated as "× (possibility of production line contamination)", and the layer containing no adhesive component was exposed and evaluated as "○ (no possibility of production line contamination)". The evaluation results are shown in Table 1.

[0186] When using adhesive tape for connection, it is generally not easy to cause peeling due to cohesive failure. The separation of metal materials A and B is easily caused by interface peeling. In this case, after the failure (that is, after the separation of metal materials A and B), the bonding surface is exposed.

[0187] Examples 1 to 4 all utilize the phase change (solid to liquid to solid) of a film with thermoplastic resin as the main component to produce a connector. Since the metal materials A and B are bonded using a mechanism different from adhesion, the above evaluations are all "○ (no possibility of production line contamination)".

[0188]

[0189] Industrial Availability

[0190] The present invention is suitably applied to, for example, applications for connecting frame materials in a production line for LED lead frames and applications for connecting substrate materials in a production line for flexible printed substrates, but is not limited to these exemplified applications.

[0191] Description of the accompanying drawings

[0192] 1: Metal material A

[0193] 2: Metal material B

[0194] 3: Thin film (thin film constituting the interconnect)

[0195] 4: Overlapping

[0196] 5: End A

[0197] 6: End B

[0198] 7: Single-sided tape

Claims

1. A metal material connection body, comprising an overlapping portion formed by overlapping an end portion A of a metal material A and an end portion B of a metal material B via a film mainly composed of a thermoplastic resin, The film is a film that has been melted and solidified at the overlapping portion. 2 . The connected body of metal materials according to claim 1 , wherein the metal material A and the metal material B are at least one selected from a metal plate having a thickness of 1 mm or less and a metal foil having a thickness of 1 mm or less. 3 . The connected body of metal materials according to claim 1 , wherein the metal material A and the metal material B are in a strip shape, and the metal material A and the metal material B are connected in a continuous manner in a length direction. 4 . The connected body of metal materials according to claim 3 , wherein the metal material A and the metal material B are coiled materials obtained by winding at least one selected from a metal plate and a metal foil into a coil shape. 5 . The metal material connection body according to claim 1 , wherein the thin film extends over the entire surface of the overlapping surface of the end portion A and the end portion B and is interposed therebetween. The metal material connection body according to claim 1 , wherein the thermoplastic resin is an amorphous thermoplastic resin. 7 . The metal material connection body according to claim 6 , wherein the amorphous thermoplastic resin is at least one selected from thermoplastic epoxy resins and phenoxy resins. 8 . The metal material connection body according to claim 7 , wherein the amorphous thermoplastic resin is an amorphous thermoplastic resin having an epoxy equivalent of 1,600 or more, or an amorphous thermoplastic resin containing no epoxy group.

9. The metal material connection body according to claim 1, wherein the film has an adhesive. The adhesive performs a temporary fixing function of the film but does not perform a bonding function.

10. A method for connecting metal materials, comprising: connecting the metal material A and the metal material B by melting and solidifying an overlapping portion formed by overlapping an end portion A of a metal material A and an end portion B of a metal material B with a film mainly composed of a thermoplastic resin therebetween. 11 . The method for connecting metal materials according to claim 10 , wherein the thickness of the film is 10 μm to 3 mm.

Citation Information

Patent Citations

  • Method of splicing a first roll material and a second roll material

    JP2016175768A